SOCIAL AND PEDAGOGICAL FACTORS OF ENSURING STUDENTS' SUCCESS IN EDUCATION (BASED ON THE EXAMPLE OF INTERNATIONAL ASSESSMENT STUDIES) (Scientific journal of the Fergana State University, 2024)
The article analyzes the socio-pedagogical factors of ensuring the success of students in education. Scientific analysis is based on the example of international evaluation studies.